Portrait photograph of an unidentified man (St. Albans, VT) - Thayer, Alexander Wheelock, 1817-1897 (previous owner):::Collector::::::::::::; Styles' Photograph Gallery:::Photographer:::::::::::: (United States; Styles' Photograph Gallery; St. Albans, VT, 2023)
Portrait photograph of an unidentified man (undated) by Styles' Photograph Gallery, People's Bock, Main St., St. Albans, VT, from the personal collection of Alexander Wheelock Thayer.